The role of behavioral finance dimensions in achieving entrepreneurial confidence - Rafeeq, Ashty; Noree, Range (Humanities Journal of University of Zakho, 2020)
The aim of the research is to identify the impact of the Behavioral Financial dimensions represented by (financial knowledge, financial attitudes, and behavioral factors) on entrepreneurial confidence. Number of companies and exchange offices in Dohuk Governorate were selected to conduct the field side of the research and the sample included (73) of managers in these companies and offices. The questionnaire is a main tool for data collection in the field side, after analyzing by the statistical program (SPSS V. 21) the research reached a set of conclusions, the most important is that there are significant effect of the behavioral financial dimensions on the Entrepreneurial confidence, as well as the presence of an insignificant effect of behavioral factors on entrepreneurial confidence at the sub-level, the research suggested a set of proposals, the most important is to activate the mechanisms of acquiring financial knowledge and financial attitudes and adopting them as they contribute to enhancing entrepreneurial confidence.